PEMAHAMAN STRUKTUR KALIMAT DIHUBUNGKAN DENGAN KOMPETENSI PEMRODUKSIAN BAHASA INGGRIS - Kurnia Idawati; Nurul Fitriani; Eka Yuniar Ernawati (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
Learning a foreign language, in this case English, usually means learning to speak in that language while understanding it. Therefore, language learning always involves two elements, namely comprehension and production. Both elements are closely related to the study of language learning performance, especially in foreign language learning. Related to that, a quantitative research was conducted over 33 learners of English in order to find out the extent to which the learners understood the structure of simple English sentences related to their ability to produce English sentences. Research data was obtained through 2 kinds of tests. The data about comprehension was in the form of true or false cloze-test of totaling 50 simple sentences with the argument structures. While the data of production was in the form of written tests of simple sentence constructions based on pictures and instructions about the pictures. Both of the tests used a number of verbs most commonly remembered by the students of English Department, Darma Persada University. The result of the research showed that their comprehension level was 65.64% with a variation in the distribution score between them was 8.79, and their production was 28.36% with a standard deviation of production of 17.37. The gap between the level of comprehension and the level of production was relatively large which means that the average production competency of the subjects was below their comprehension competency.